Assessment of planning and programming for capital projects at the national and agency levels - Epictetus E. Patalinghug (Philippine Institute for Development Studies (PIDS), 2017)
This study assesses the existing planning and programming systems for capital projects at the national and agency levels, examines the experiences of other countries in planning and programming capital projects, and presents recommendations to improve planning and programming systems in the country. The study employs a combination of document review of public investment planning and programming process, a comparative analysis of international experiences, and key informant interviews.The study shows that the country's current planning and programming systems have strengths and weaknesses. The strengths are the recent reform orientation of the oversight agencies and their policy coordination, while weaknesses are the inconsistency in the oversight program and output indicators, and the institutional weakness of the project approval process. The study suggests that international best practices be adopted, and recommends institutional reforms such as establishment of online public investment project database as well as a multiyear planning and budgeting system fully costed and coordinated with the budget process and consistent with the long-term fiscal projections which are regularly updated and reviewed, among others.
Keywords: 330; infrastructure; capital projects; public investment planning; planning and programming systems; infrastructure development; infrastructure projects